Lean business models change process in digital entrepreneurship. Issue 7 (14th October 2019) - Balocco, Raffaello; Cavallo, Angelo; Ghezzi, Antonio; Berbegal-Mirabent, Jasmina
Abstract : Purpose: Business model change (BMC) is a process new ventures are frequently involved in, especially in dynamic environments like the digital industry: copying with it is a key issue for entrepreneurs attempting to shorten the transition between current and new business models (BMs) and avoid losses in terms of revenue, image and customer retention, while acquiring experience and validated learning in the process. The purpose of this paper is to propose a lean framework to support digital new ventures in the BMC process. Design/methodology/approach: The study builds its contribution on two pillars: a review on BM and the lean thinking theories, and a multiple case study on three digital new ventures which underwent BMC. Findings: The study shows how BMC in a digital context can beneficially follow lean principles, and how these principles can be integrated in an original lean framework to experiment on, validate and subsequently change a BM. Originality/value: The authors provide the "single minute exchange of die" for BMC framework that extends and complements lean startup approaches to further relate lean thinking and BMC, thus operationalizing the process of BM experimenting and validation that enables change.